Protestantische Kirchen Hollands und Dekolonisation Indonesiens: Stellungnahmen aus der Nachkriegszeit - Scharffenorth, Ernst-Albert (Kirchliche Zeitgeschichte, 1989)
The political decolonisation of the former dutch colony is treated as a political challenge for three protestant churches: the big Dutch Reformed Church (NHK), the little reformed free church (GKN) and the tiny lutheran church (ELK). In 1945/46, these churches hat to react to the dutch government's policy aiming at decolonisation but not independence (which was just claimed by Sukarno). The Churches, however, were not only confronted with these different policies. They had to consider the attitude of the dutch political opposition, too. Here it was especially the group of protestant which opposed any policy changing the status quo. There were statements of all three churches and in every case the mission played an important part. The NHK, however, was the only church which gave full support to the official dutch policy of decolonisation and - though in cautious terms - payed respect to the Indonesian's right of self-determination. In consequence of the influence of van Ruler, who represented the radical theocratic tradition, this statement was not free of eurocentric reasoning and did not do right to the ecumenical dimension of the church. The final thesis says: not only the lutheran doctrine of the two kingdoms, but also corresponding reformed concepts are to be questioned.